Banalitas Intelektual Dalam Dunia Pendidikan Perguruan Tinggi Suatu Kajian Filsafat Ilmu - Anastasia Jessica Adinda S. (Arete, 2013)
This paper discusses the educational problem in Indonesian higher education, which is called by Heru Nugraha as intellectual banality. Intellectual banality is a situation which is marked by unconscious superficiality of thinking and degradation of intellectual and academic quality. This paper aims to find out the causes of intellectual banality from the lens of the philosophy of science. We took this perspective since the educational practices carry out the assumption of how to view the science. Intellectual banality firstly happens due to the view which tends to put more emphasis on the quantity to measure the intellectual quality. This is viewed as the romanticism of inductive methods. The second cause is the neglection of the objective of science to reach the prosperity of all human beings, not only for some communities. Therefore, the changing views on how to measure the quality of education qualitatively need conducting to improve the higher education